2005
DOI: 10.1021/ja054108w
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Growth of Single-Walled Carbon Nanotubes by Water Plasma Chemical Vapor Deposition

Abstract: Preferential growth of pure single-walled carbon nanotubes (SWNTs) over multi-walled carbon nanotubes (MWNTs) was demonstrated at low temperature by water plasma chemical vapor deposition. Water plasma lowered the growth temperature down to 450 degrees C, and the grown nanotubes were single-walled without carbonaceous impurities and MWNTs. The preferential growth of pure SWNTs over MWNTs was proven with micro-Raman spectroscopy, high-resolution transmission electron microscopy, and electrical characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 12 publications
5
79
0
Order By: Relevance
“…7,8 The growth condition for the nanotube forest was the same as for the nanotube network except the catalyst substrate. The catalyst-formed substrates were placed on a quartz holder and then heated up to 450 o C for 300 sec in water atmosphere which resulted in an increase of ~5 mTorr in the base pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 The growth condition for the nanotube forest was the same as for the nanotube network except the catalyst substrate. The catalyst-formed substrates were placed on a quartz holder and then heated up to 450 o C for 300 sec in water atmosphere which resulted in an increase of ~5 mTorr in the base pressure.…”
Section: Methodsmentioning
confidence: 99%
“…6 Recently we reported that random networks of highly pure SWNT were grown on silicon and glass substrates at 450 and 550 o C, respectively, by water plasma CVD using methane and water vapor wherein the catalyst nanoparticles of iron were formed by burning a photoresist film containing a catalyst precursor of ferrocene. [7][8][9][10] Here, we demonstrate the SWNT forest grown at 450 o C by water plasma CVD using ultrathin iron on alumina supporting film. The catalyst for SWNT forest and the role of water are discussed.…”
Section: Introductionmentioning
confidence: 91%
“…• C) [12][13][14][15]. This contribution presents CVD synthesis of CNTs in vacuum conditions at low pressure, with acetylene (C 2 H 2 ) as a carbon feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental details are previously reported. 9,11 For sample II, after SWNT growth, ALD of ZnO was performed at 250°C for 70 cycles in order to form ZnO nanoparticles. Figure 4͑a͒ shows the emission current variation with measurement time of the two samples.…”
mentioning
confidence: 99%
“…Figure 4͑b͒ shows FN plots of the two samples. Assuming that work functions of the nanotube tips are 4.8 eV, 9 the field enhancement factor ͑␥ II ϳ 960͒ of sample II, which can be calculated from the slop of the FN plot, 9,11 is smaller than that ͑␥ 1 ϳ 2200͒ of sample I. The lower field enhancement factor of sample II is possibly due to the larger effective diameter of the ZnO-nanoparticle-coated nanotubes than that of the uncoated SWNTs.…”
mentioning
confidence: 99%